The Problem of Criminalization of Commercial Sexual Workers and Users of Prostitution Services - Rianda Dirkareshza; Eka NAM Sihombing; Rosalia Dika Agustanti (Jurnal Penelitian Hukum De Jure, 2022)
Prostitution is a complex problem because it intersects with so many aspects, especially in women’s rights. However, the complexity of the problem is not accompanied by legal certainty of regulations regarding prostitution. This paper aims to find out and understand how the problem of criminalization of prostitutes and users of prostitution services in Indonesia. This research method is normative juridical law research with a concept and legislation approach. Data used secondary data consisting of primary, secondary, and tertiary materials. The result found is a legal vacuum related to the regulation of prostitution actions so that prostitutes and users of prostitution services often escape the legal snare. The need for criminalization as a countermeasure against users of prostitution services that are key in the practice of prostitution and protecting women’s rights. As well as countermeasures by providing rehabilitation for prostitutes and in them to have skills and not fall back into the vortex of prostitution practices.